A Report from the International Scientific Conference DLCC2018, 15–16 October 2018, Poland - Smyrnova-Trybulska, Eugenia (International Journal of Research in E-learning, 2018)
The 10th edition of the International Scientific Conference DLCC2018: Theoretical and Practical Aspects of Distance Learning (www.dlcc.us.edu.pl) was held under the theme “E-learning and smart learning environment for preparing the specialists of new generation” and included reports from the IRNet project. The conference was held on 15–16 October 2018 in Wisła. It was organised by the Faculty of Ethnology and Educational Science at the University of Silesia in Cieszyn. The co-organisers were: the University of Ostrava (the Czech Republic); the Silesian University in Opava (the Czech Republic); the Constantine Philosopher University in Nitra (Slovakia); the Twente University (the Netherlands); the University of Extremadura (Spain); the Curtin University in Perth (Australia); the Borys Grinchenko Kiev University (Ukraine); the Herzen State Pedagogical University of Russia (Russia); the Dneprodzerzhinsk State Technical University (Ukraine); Ministry of Science and Higher Education, Poland; Polish Pedagogical Association, Branch in Cieszyn; Polish Scientific Association of Internet Education; IADIS – International Association for Development of the Information Society; and SEA – Polish Academic E-learning Association.